Phenology: an integrative environmental science - Schwartz, Mark D. (Springer Netherlands, 2013)
Phenology refers to recurring plant and animal life cycle stages, such as leafing and flowering, maturation of agricultural plants, emergence of insects, and migration of birds. It is also the study of these recurring events, especially their timing and relationships with weather and climate. Phenological phenomena all give a ready measure of the environment as viewed by the associated organism, and are thus ideal indicators of the impact of local and global changes in weather and climate on the earth's biosphere. Assessing our changing world is a complex task that requires close cooperation from experts in biology, climatology, ecology, geography, oceanography, remote sensing, and other areas. Like its predecessor, this second edition of Phenology is a synthesis of current phenological knowledge, designed as a primer on the field for global change and general scientists, students, and interested members of the public. With updated and new contributions from over fifty phenological experts, covering data collection, current research, methods, and applications, it demonstrates the accomplishments, progress over the last decade, and future potential of phenology as an integrative environmental science.